Examining the Impact of Personal Factors on Scores on the Self‐Determination Inventory: Adult Report in Adults with Disabilities. Issue 2 (2nd September 2020) - Hagiwara, Mayumi; Shogren, Karrie A.; Rifenbark, Graham G.
Abstract: Background: Self‐determination develops across the life course and plays an important role in the lives of people with disabilities throughout childhood, adolescence, and into adulthood. Self‐determination is also assumed to be an enduring characteristic which can be meaningfully assessed over time with development. Further, researchers have consistently found that personal factors, such as age, gender, race/ethnicity, and disability status may impact the development and expression of self‐determination for people with disabilities. Recently, the Self‐Determination Inventory: Adult Report (SDI:AR), a self‐report measure, was developed to assess self‐determination for adults with and without disabilities ages 18 and over. However, there has not been any comprehensive studies examining the impact of personal factors on self‐determination of adults with and without disabilities as measured by the SDI:AR. Such work will inform the impact of personal factors on self‐determination of adults with and without disabilities. Specific Aims: The purpose of this study was to analyze data from the SDI:AR validation study to examine the impact of personal factors (age, gender, and disability label) on the expression of self‐determination in adults with and without disabilities. Method: This study used multilevel linear models, and the sample included 541 adults with and without disabilities ages 18 and 71. Findings: Results showed personal factors impacted overall self‐determination for adults with and without disabilities in complex ways. In general, adults without disabilities scored higher than adults with disabilities, especially adults with intellectual disability. Results also suggested that the SDI:AR could be a meaningful tool to measure adult self‐determination. Discussion: Considering the significant yet complex impact on adult self‐determination, it is critical to provide supports and opportunities for self‐determination throughout adulthood by taking personal factors into account.